Associative business management model for PROACHIRKO , Huanangui Comm unity, Peru - Buse Thorne, Eduardo (2015)
This research was conducted for Productores Asociados de Chirimoya de Kalidad Óptima (PROACHIRKO); agricultural association created in 2009 with fifty partners, located in the district of Leoncio Prado province of Huaura, Lima Region. They are dedicated to the cultivation and harvesting of cherimoya in different natural conditions. The research aims to develop an action plan based on a proposed model of business management partnership that includes the coordinated participation of public, private and academic sectors together, with an integration based on trust; however, competitiveness should improve and expand its offerings in the global market. Through research PROACHIRKO will be analyzed: their productive, administrative, associative aspects characteristics are identified, among others, to propose a model that will allow them to ensure their permanence in the local market and capitalize on the existing favorable business environment for exports.